HEMODYNAMICS OF THE BASIN OF THE LEFT RENAL VEIN AND THE EFFECT OF ARTERIAL STRUCTURES ON IT (SUPERIOR MESENTERIC ARTERY AND AORTA) - Путинцев, Александр Михайлович; Струкова, Оксана Анатольевна; Францев, Роман Сергеевич; Константинова, Наталья Николаевна; Петрова, Мария Альбертовна (Medicine in Kuzbass, 2024)
The syntopy of the aorta and superior mesenteric artery (VBA) in relation to the left renal vein (LVV), as well as the total effect of pulsating pressure of the aorta and superior mesenteric artery on the hemodynamics of the left renal vein were studied by applying hydrodynamic and mathematical research methods. It has been shown that the outflow from the left renal vein basin is affected not only by venous vessel compression, but also by pulse pressure. Simultaneous pulsation of the aorta and artery creates a pulsating pressure support in the vein, inhibiting blood flow in it and causing fluctuations in the speed of blood movement downward to the contact zones of the aorta and artery and upward beyond the contact zones. With a high probability, the described phenomenon will eventually lead to pathologies of individual sections of the vein and the vessels coming out of it, as well as organs from which the outflow will be disrupted.